Pan-Cancer Analysis of Immune Cell Infiltration Identifies a Prognostic Immune-Cell Characteristic Score (ICCS) in Lung Adenocarcinoma - Zuo, Shuguang; Wei, Min; Wang, Shiqun; Dong, Jie; Wei, Jiwu (Frontiers in Immunology, 2020)
Background: The tumor microenvironment (TME) consists of heterogeneous cell populations, including malignant cells and nonmalignant cells that support tumor proliferation, invasion, and metastasis through extensive crosstalk. The intra-tumor immune landscape is a critical factor influencing patient survival and response to immunotherapy. Methods: Gene expression data were downloaded from The Cancer Genome Atlas and Gene Expression Omnibus databases. Immune cell infiltration was determined by single-sample gene set enrichment analysis (ssGSEA) depending on the integrated immune gene sets from published studies. Univariate analysis was used to determine the prognostic value of the infiltrated immune cells. LASSO regression was performed to screen for the most survival-relevant immune cells. An immune-cell characteristic score (ICCS) model was constructed by using multivariate Cox regression analysis. Results: The immune cell infiltration patterns across 32 cancer types were identified, and patients in the high immune cell infiltration cluster had worse overall survival (OS) but better progression-free interval (PFI) compared to the low immune cell infiltration cluster. However, immune cell infiltration showed inconsistent prognostic value depending on the cancer type. High immune cell infiltration indicated a worse prognosis in LGG, GBM, and UVM, and favorable prognosis in ACC, CESE, CHOL, HNSC, LIHC, LUAD, SARC, and SKCM. LUAD prognosis was significantly influenced by the infiltration of 13 immune cell types, with high infiltration of all but Th2 cells correlating with a favorable prognosis. An ICCS model based on 6 most survival-relevant immune-cell populations was generated that classified patients into low- and high-ICCS groups with good and poor prognosis respectively. The multivariate and stratified analysis further revealed that the ICCS was an independent prognostic factor for LUAD. Conclusions: The infiltration of immune cells in 32 cancer types was quantified and considerable heterogeneity was observed in the prognostic relevance of these cells in different cancer types. An ICCS model was constructed for LUAD with competent prognostic performance, which can further deepen our understanding of the tumor microenvironment of lung adenocarcinoma and can have implications for immunotherapy.